ASPECTS OF LEGAL PROTECTION AND LEGAL CERTAINTY FOR MEDICAL PERSONNEL AND HEALTH WORKERS IN HEALTH SERVICE PRACTICES IN HOSPITALS - Marzuki; Sumarno; Irsyam Ridawati (RADJA PUBLIKA, 2025)
This study aims to analyze legal protection and legal certainty for medical personnel in the practice of health services in hospitals, by highlighting various regulations that regulate the rights and obligations of medical personnel, doctors, and hospitals in providing health services. Legal protection for medical personnel is regulated in Law Number 17 of 2023 concerning Health, especially in Article 273, which guarantees the right of medical personnel to obtain legal protection while acting in accordance with applicable professional standards and procedures. This article provides legal certainty for medical personnel to be able to carry out their duties with a sense of security and avoid unfounded legal threats, as long as medical actions are taken in accordance with the principles of professionalism and ethics. The rights and obligations of doctors to patients are regulated in various provisions in this law, with emphasis on Article 274 which regulates the obligation of doctors to provide safe, quality, and in accordance with applicable professional standards. Doctors are required to provide a clear and thorough explanation to the patient about the medical procedure to be performed and the potential risks, and obtain approval from the patient or his family before performing the medical procedure. This aims to ensure that patients make informed decisions and that there is no violation of the patient's right to bodily autonomy. Furthermore, the hospital's obligation to provide protection for medical personnel is regulated in Article 273 and Article 274. Hospitals as health service providers have the responsibility to create a safe working environment for medical personnel and provide protection from potential physical and legal threats that are not in accordance with existing regulations. Hospitals are also obliged to ensure that every medical action carried out by medical personnel is in accordance with the applicable standard operating procedures (SOPs) and provides facilities to resolve medical disputes that may arise, either through mediation or appropriate legal processes. Through this study, it is hoped that it can be revealed how effective the legal protection provided to medical personnel in hospitals, as well as how hospitals' obligations are in supporting the sustainability of safe and professional medical practices. In addition, this study also aims to provide recommendations related to improvements in the legal protection system for medical personnel, in order to create better legal certainty in the practice of health services in hospitals